Multidimensional measures of impulsivity in obsessive-compulsive disorder: cannot wait and stop. - Sung Yun Sohn; Jee In Kang; Kee Namkoong; Se Joo Kim (PLoS ONE, 2014)
OBJECTIVE: Although the relationship between obsessive compulsive disorder (OCD) and impulsivity has long been debated, impulsivity has not been systematically examined in clinical samples of OCD. Meanwhile, recent findings suggest that impulsivity is multi-dimensional construct that can be examined through several constructs. Therefore, this study is aimed to evaluate multiple facets of impulsivity in OCD. METHOD: The recruitment includes 80 OCD and 76 healthy control participants. Participants completed a test battery comprising three behavioral tasks of stop signal task (SST), delay discounting task (DDT) and balloon analog risk test (BART), and one self-report measure of the Barratt Impulsiveness scale (BIS-11). RESULTS: OCD subjects showed significantly lower stop signal reaction time of SST reflecting higher action impulsivity and higher delay discounting parameter of DDT suggesting increased choice impulsivity but significantly lower adjusted mean pump of BART implying lower risk taking propensity of BART than healthy control. CONCLUSION: Increased Action and choice impulsivity, and decreased risk taking propensities were found in OCD. These findings seem to be consistent with clinical characteristics of OCD such as greater preference for or avoid risky situations (avoidance), inability to wait tension relief may provoke safety behaviors (compulsion) and inability to stop already started behaviors (repetition).